2014
DOI: 10.1016/j.jesf.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of concurrent training on inflammatory markers and expression of CD4, CD8, and HLA-DR in overweight and obese adults

Abstract: The number of people who are overweight or obese is increasing worldwide and the quality of life of these people can be affected by their condition. Physical training has been studied in obese patients and is correlated with low-grade inflammation and alterations in the immune system. This study investigated the effect of concurrent training on anthropometric, inflammatory, and immunological parameters in overweight and obese adults. Fourteen sedentary volunteers (men and women) with a body mass index between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 46 publications
0
17
1
1
Order By: Relevance
“…The contemporary literature suggests that exercise has systemic effects on immune function that can counteract the chronic low grade inflammation induced by physical inactivity and obesity . Although reductions in body fatness are widely recognized to induce some of the anti‐inflammatory effects of exercise training, changes in cellular immune function are independently of changes in body fat .…”
Section: Introductionmentioning
confidence: 99%
“…The contemporary literature suggests that exercise has systemic effects on immune function that can counteract the chronic low grade inflammation induced by physical inactivity and obesity . Although reductions in body fatness are widely recognized to induce some of the anti‐inflammatory effects of exercise training, changes in cellular immune function are independently of changes in body fat .…”
Section: Introductionmentioning
confidence: 99%
“…IL10 is an anti-inflammatory cytokine which is impaired in obesity (26). Here, IL10 remained unchanged after all ex.…”
Section: Resultsmentioning
confidence: 73%
“…Interestingly, Colato et al, 37 found increased levels of TNF-α and CRP after 12 weeks of concurrent training in 41 overweight / obese patients. Although there was an improvement in body composition and an increase in T-cell proliferation, the authors emphasize that exercise progression may be physiologically stressful for these patients, as demonstrated by inflammatory markers.…”
Section: Discussionmentioning
confidence: 98%